2020
DOI: 10.1177/1758835920922034
|View full text |Cite|
|
Sign up to set email alerts
|

Combination therapy with dendritic cell vaccine and programmed death ligand 1 immune checkpoint inhibitor for hepatocellular carcinoma in an orthotopic mouse model

Abstract: Background: Hepatocellular carcinoma (HCC) is among the most common and lethal human cancers worldwide. Despite remarkable advances in treatment, high mortality in HCC patients remains a big challenge. To develop novel therapeutic strategies for HCC is thus urgently needed to improve patient survival. Dendritic cells (DC)-based vaccines can induce tumor-specific immunity and have emerged as a promising approach for treating HCC patients; however, its effectiveness needs to be improved. Recently, blockade of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…In addition, PD-1 blockade increased the efficacy of DC vaccines when combined with tumor antigens and CCL21 in a mouse lung-cancer model ( 109 ). Furthermore, a combined treatment of DC vaccine and PD-L1 blockade improved overall survival and tumor rejection in a murine hepatocellular carcinoma model ( 110 ).…”
Section: Vaccinesmentioning
confidence: 99%
“…In addition, PD-1 blockade increased the efficacy of DC vaccines when combined with tumor antigens and CCL21 in a mouse lung-cancer model ( 109 ). Furthermore, a combined treatment of DC vaccine and PD-L1 blockade improved overall survival and tumor rejection in a murine hepatocellular carcinoma model ( 110 ).…”
Section: Vaccinesmentioning
confidence: 99%
“…Rare preclinical data exist on vaccine-α-PD-L1 combinations. A recent study described prolonged survival and increased tumor cell apoptosis in a hepatocellular carcinoma model treated with a combined DC vaccine and α-PD-L1 inhibitor [46], supported by findings from Ji et al, reporting reactivation of neoantigen-specific CTL by combined α-PD-L1 peptide vaccination [47]. Likewise, Sun et al found enhanced tumor-antigen-specific immunity upon combined vaccine-PD-L1-blockade [48].…”
Section: Discussionmentioning
confidence: 70%
“…Rare preclinical data exist on vaccine-α-PD-L1 combinations. A recent study described prolonged survival and increased tumor cell apoptosis in a hepatocellular carcinoma model treated with a combined DC vaccine and α-PD-L1 inhibitor [42]. Likewise, Sun et al found enhanced tumor-antigen-speci c immunity upon combined vaccine-PD-L1-blockade [43].…”
Section: Discussionmentioning
confidence: 98%